Spectral properties of gamma-ray bursts observed by the Suzaku wide-band all-sky monitor. (4th June 2019) - Ohmori, Norisuke; Yamaoka, Kazutaka; Yamauchi, Makoto; Urata, Yuji; Ohno, Masanori; Sugita, Satoshi; Hurley, Kevin; Tashiro, Makoto S; Fukazawa, Yasushi; Iwakiri, Wataru; Katsukura, Daisuke; Kokubun, Motohide; et al.
Abstract: We have systematically studied the spectral properties of 302 localized gamma-ray bursts (GRBs) observed by the Suzaku wide-band all-sky monitor (WAM) from 2005 August to 2010 December. The energy spectra in the 100–5000 keV range integrated over the entire emission and the 1 s peak were fitted by three models: a single power law, a power law with an exponential cutoff (CPL), and the GRB Band function (GRB). Most of the burst spectra were well fitted by a single power law. The average photon index α was −2.11 and −1.73 for long and short bursts, respectively. For the CPL and GRB models, the low-energy and high-energy photon indices (α and β) for the entire emission spectra were consistent with previous measurements. The averages of the α and β were −0.90 and −2.65 for long-duration GRBs, while the average α was −0.55 and the β was not well constrained for short-duration GRBs. However, the average peak energy E peak was 645 and 1286 keV for long- and short-duration GRBs respectively, which are higher than previous Fermi/GBM measurements (285 keV and 736 keV). The α and E peak of the 1 s peak spectra were larger, i.e., the spectra were harder, than the total fluence spectra. Spectral simulations based on Fermi-GBM results suggest that the higher E peak s measured by the Suzaku WAM could be due to detector selection bias, mainly caused by the limited energy range above 100 keV.